Piccole e micro imprese italiane tra crisi e vincoli finanziari: un’indagine empirica - Pace, Roberta (Piccola Impresa / Small Business, 2013)
Small and micro enterprises have to face stringent financial constraints and, in recent years, they also have to face the effects of the financial crisis and a drop of liquidity. Starting from theoretical and empirical literature reviews about the main financial difficulties of SMEs and about the real effects of financial crises, the paper investigates the situation of the Italian micro and small firms financial structure. The aim is to verify, analyzing the balance sheets of 15.779 companies, which are characteristics and financial problems of Italian firms and if they are able to create value during a crisis.